2017
DOI: 10.1007/s12017-017-8444-z
|View full text |Cite
|
Sign up to set email alerts
|

rs3851179 Polymorphism at 5′ to the PICALM Gene is Associated with Alzheimer and Parkinson Diseases in Brazilian Population

Abstract: Alzheimer's (AD) and Parkinson's diseases (PD) share clinical and pathological features, suggesting that they could have common pathogenic mechanisms, as well as overlapping genetic modifiers. Here, we performed a case-control study in a Brazilian population to clarify whether the risk of AD and PD might be influenced by shared polymorphisms at PICALM (rs3851179), CR1 (rs6656401) and CLU (rs11136000) genes, which were previously identified as AD risk factors by genome-wide association studies. For this purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…hsa_circ_0023919 is located in PICALM gene that is involved in clathrin-mediated endocytosis at neuromuscular junctions [26] and single nucleotide polymorphism upstream of the gene has been associated with Alzheimer’s disease [40]. This circRNA was downregulated in microarray analysis and qPCR results also confirmed this.…”
Section: Discussionmentioning
confidence: 83%
“…hsa_circ_0023919 is located in PICALM gene that is involved in clathrin-mediated endocytosis at neuromuscular junctions [26] and single nucleotide polymorphism upstream of the gene has been associated with Alzheimer’s disease [40]. This circRNA was downregulated in microarray analysis and qPCR results also confirmed this.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, most studies have focused on the role of PICALM in PD; however, none were able to investigate the effect of this gene on cognitive impairment 13,16‐18 . Santos‐Rebouças and colleagues 13 performed a case‐control study in a Brazilian population of 174 patients with late‐onset AD, 166 patients with late‐onset PD, and 176 controls and showed that the rs3851179 T allele represented a significant protective factor for PD with an OR similar to AD. Nonetheless, the plausible interaction of PICALM and APOE was only assessed in the AD cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The PICALM gene encodes the clathrin adaptor protein involved in clathrin‐mediated endocytosis, which is an essential step in the intracellular trafficking of proteins, lipids, growth factors, and neurotransmitters. In recent years, the potential role of PICALM rs3851179 in the pathogenesis of PD has been assessed using ethnically diverse study populations, but the findings have been mixed 13‐18 …”
Section: Introductionmentioning
confidence: 99%
“… 31 2017 Colombia Mixed population (Caucasian, African and American) 280 357 PCR C/T Santos-Reboucas et al . 32 2017 Brazil Mixed population (Caucasian, African and mulatto) 174 175 TaqMan CC/CT/TT Ferrari et al . 15 2012 UK Mixed population (Caucasian and African) 342 277 TaqMan C/T Gu et al .…”
Section: Methodsmentioning
confidence: 99%